Anion-dependent structural variations and charge transport property analysis of 4′-(3-pyridyl)-4, 2′:6′, 4′′-terpyridinium salts. Issue 19 (30th April 2021) - Hossain, Anowar; Dey, Arka; Seth, Saikat Kumar; Ray, Partha Pratim; Ortega-Castro, Joaquín; Frontera, Antonio; Mukhopadhyay, Subrata
Abstract : Anion-dependent structural variations and charge transport analysis of three 4′-(3-pyridyl)-4, 2′:6′, 4′′-terpyridinium salts are reported. They exhibit pronounced photosensing behavior when illuminated using visible light. Abstract : Terpyridinium salts of hydracids [PTPH3 ](Br)3 ·H2 O (1 ), [PTPH3 ](Cl)3 ·2H2 O (2 ) and oxoacid [PTPH3 ](ClO4 )3 ·H2 O (3 ) (PTP = 4′-(3-pyridyl)-4, 2′:6′, 4′′-terpyridine) were synthesized and characterized using single crystal X-ray diffraction analyses. The crystallographic analysis reveals that the π + ⋯π, π + ⋯π +, anion⋯π and anion⋯π + interactions play a crucial role in the stabilization of the self-assembled structure, which in turn is responsible for enhancing the dimensionality of all the compounds. All the compounds confirm their usefulness as optoelectronic devices owing to the pronounced electrical conductivity and photosensitivity. Experimental and theoretical observations clarify an increase in the electrical conductivity on irradiation compared to dark conditions, especially in 3 .